Influence of multigrain premix on nutritional, in-vitro and in-vivo protein digestibility of multigrain biscuit - Ashwath Kumar, K. (J Food Sci Technol, 2018)
Effect of addition of multigrain premix (MGP) prepared using a combination of cereals, pulses and oilseeds at 40% level, on nutritional properties of multigrain biscuit, its in-vitro and in-vivo protein digestibility and protein profiling were studied. The incorporation of MGP significantly increased the protein content (from 7.37 to 16.61%), insoluble dietary fiber (from 1.71 to 6.67%), soluble dietary fiber (from 0.46 to 2.42%). The significant increase in the levels of isoleucine (ND-34.79%), methionine (0.04 to 7.65%), tryptophan (0.22 to 5.95%) valine (0.38 to 16.58%), lysine (0.36 to 7.32%), and threonine (0.51 to 7.2%) was observed, whereas fatty acid profile of MGP incorporated biscuits showed increased polyunsaturated fatty acids and decreased saturated fatty acids. The vitamin–mineral profile of MGP incorporated biscuits showed increased the thiamin (0.07–0.21 mg/100 g), riboflavin (0.09–0.28 mg/100 g), calcium (12.89–45.28 mg/100 g) and iron (1.13–3.47 mg/100 g) contents. The in-vitro protein digesibility of multigrain and control biscuits indicated that the proteins present in multigrain biscuits had high digestibility (71.73%) as compared to control biscuit (38.13%). The in-vivo studies indicated that, the protein quality of multigrain biscuits was comparable with casein protein with high protein efficiency ratio of 3.02. The electrophoretic pattern of multigrain biscuits showed subunit molecular weight distribution of different protein units and aggregation of protein bands at high molecular weight region of 85 to 166 kD. The outcome of the study indicated the possibility of utilising MGP to improve the overall nutritional quality of biscuits.